การพัฒนาตนเองของหัวหน้าหอผู้ป่วยโรงพยาบาลชุมชน - ชูชีพ มีศิริ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
To define the meaning and the experience of self development of the head nurses in the community hospitals. Nineteen key informants from the professional nurses who had at least one year working experience were selected as the head nurses in the study. The target community hospitals located in an office of public health in the central region of Thailand were purposively selected as the research sites. Data collecting method involved in-depth interview by tape recording and were transcribed verbatim and later analyzed by using a Colaizzi s process. The study found that the head nurses gave the meaning of self development were self improving in both of knowledge and skills in management along with knowledge and skills in nursing practice in order to get the acceptation from immediate superior and subordinate. Desired to learn was the other meaning, because of dynamic knowledge, motivated for self development to adjust themselves for health service. The experience for self development found that the motivation for development began after they were the head nurses which included the perception of responsibility, perceived to have higher knowledge and skills than subordinates, desired to be a role model for nursing practice and had to teach and to supervise for health care team. In addition, the motivation for self development was to perdeive that they were not ready to work as head nurses and they have to get supporting from the organization and their families. In addition, the self development methods of the head nurses were the knowledge developoment by formal and informal learning, mind development by self assessment, self control and relaxation, and the other method was health development by exercises and diet control. The important finding of this study was the head nurses perceived that they lacked of supporting from their organizations and superiors. Therefore, in order to improve their knowledge and skills in management, the organization should train them prior to be the head nurses.